Punctuation Errors by The Fourth Semester Students of The English Department - Sudilah, Sudilah (Ahmad Dahlan Journal of English Studies, 2015)
AbstractÂ This paper was written based on the end-semester composition examination paper of the fourth Â semester students of the English Department, Faculty of Education And Teacher Training, Ahmad Dahlan University inÂ  Yogyakarta. The study aimed at : (1) analyzing the studentsâ errors in using punctuation marks in their composition examination paper and (2) identifying the most as well as the least frequently used punctuation marks in their composition examination paper, and (3) finding out whether there is relation between studentsâ ability in using punctuation mark and their final examination grades. Â Â Â Â Â Â Â Â  The objects of the study were 29 composition examination paper written by the fourth semester students of the academic year 2008/2009. The criteria used to identify and analyze the students âerrors were adapted from the Writerâs Bureau Handbook, the Essentials of English, and the American English Today. The results of the study indicated that : 1) there were 59 cases of errors found covering four kinds of punctuation marks â full stop (.), commas (,), apostrophe (â), and quotation mark (âÂ  â). They respectively occurred 14, 36, 5, and 4 times, 2) Of the 29 students, none used 10 to 11 kinds of punctuation marks. Only 1 student (3,44%) used 9 kinds of punctuation , 2 students (6,90) used 7 kinds,19 students (65,51%)Â  used 5 to 6 kinds and 3 students (10,34%) used 4 kinds, 4 students (13,80%) Â used 2 to 3 kinds of punctuationmarks. It could be interpreted that in the average the students were able to use 5 to 6 kinds of punctuation marks in their composition. 3) There was also a close relation between the studentsâ ability of using punctuation and their composition grades.